Factors affecting the intention to adopt internet banking services among small and medium sized-enterprises in Yemen - Al-Fahim, Nabil H; Wan Jusoh, Wan Jamaliah; Adewale, Abideen Adeyemi (Global Advanced Research Journals, 2014)
In spite of the wide adoption of Internet banking service in developed countries, its application is still low in developing countries like Yemen. The purpose of this study is to examine and investigate the main factors which influence the adoption of Internet banking services by Small and Medium Enterprises (SMEs) managers or owners in Yemen. The research framework consists of five latent variables, four exogenous variables and one endogenous variable. The exogenous variables consist of environmental factors such as ICT readiness, regulatory support, financial institution support and competitive pressure while endogenous variable comprises of intention towards Internet banking service adoption (IBSA). In addition, this study will explain how the Technology Organization Environment (TOE) framework was being used in examining the factors of Internet banking services adoption in Yemen. The hypothetical relationship was examined using structural equation modeling (SEM). The findings of the study indicated that competitive pressure was the high predictor that influence towards IBSA followed by regulatory support and financial institution support while ICT readiness was an insignificant and negative effect towards IBSA in Yemen.